Temperature stability and low dielectric loss of lithium-doped CdCu3Ti4O12 ceramics for X9R capacitor applications. Issue 17 (1st December 2019) - Zhao, Nan; Liang, Pengfei; Wu, Di; Chao, Xiaolian; Yang, Zupei
Abstract: We report that lithium doping in a CdCu3 Ti4 O12 ceramic results in the simultaneous reduction of dielectric loss at low frequency and improvement in the temperature stability while maintaining the high permittivity. Detailed microscopic morphology was studied by scanning electron microscopy (SEM). Phase compositions were studied by X-ray diffraction; dielectric properties, by Rietveld analysis, Raman spectroscopy and an impedance analyser. In addition to its grain refining effect, lithium doping intensifies the Ti–O octahedron distortion, thus enhancing polarization, which is believed to be responsible for the enhanced dielectric response. In particular, Li0.01 Cd0.99 Cu3 Ti4 O12 exhibited low dielectric loss at 1 kHz (equal to 0.033) and a relatively high dielectric constant (greater than 14, 000) in the 40 Hz–100 kHz range. Moreover, the ceramic exhibited outstanding dielectric constant stability at 1 kHz with Δε׳(T)/ε׳RT < ± 15% over a very broad temperature range (from 218 K to 598 K), which satisfies the commercial criteria of X9R capacitors.